From Measurement to Decision Making: Understanding the Nature of Educational Evaluation from the Perspective of Modern Learning - Eka Susanti; Aprina Noor Latifah; Khairunnida Khairunnida; Hasni Noor (The Future of Education Journal, 2026)
Educational evaluation is an essential component of the learning process that functions not only to measure learning outcomes but also to provide a basis for decision-making aimed at improving educational quality. This article seeks to examine the evolution of educational evaluation concepts in contemporary literature, analyze the conceptual distinctions among evaluation, assessment, measurement, and testing, and explore the contribution of evaluation to learning effectiveness in the digital era and twenty-first-century education. This study employed a qualitative approach using a library research method through the analysis of relevant scholarly literature. The findings indicate that the concept of educational evaluation has evolved from an outcome-oriented approach toward a more comprehensive, continuous, and learner-centered perspective. Evaluation encompasses a broader scope than assessment, measurement, and testing, as it involves judgment and decision-making processes based on collected data. Numerous studies demonstrate that systematically designed and continuously implemented evaluations significantly contribute to learning effectiveness by providing feedback, monitoring student progress, and improving instructional strategies. Furthermore, digital transformation has encouraged the development of technology-based evaluation practices that are more flexible, adaptive, and authentic. In the context of Islamic Religious Education, evaluation plays a crucial role in assessing students’ competencies holistically across cognitive, affective, and psychomotor domains. Therefore, the development of evaluation systems that align with the demands of twenty-first-century education is a strategic necessity for enhancing the quality of learning and education sustainably.